2016
DOI: 10.1016/j.jvs.2015.11.034
|View full text |Cite
|
Sign up to set email alerts
|

National trends in utilization and outcome of thoracic endovascular aortic repair for traumatic thoracic aortic injuries

Abstract: Introduction Endovascular repair of traumatic thoracic aortic injuries (TTAI) is an alternative to conventional open surgical repair. Single institution studies have shown a survival benefit with TEVAR, but it is not clear if this is being realized nationally. The purpose of our study was to document trends in the increase in utilization of TEVAR and its impact on outcomes of TTAI nationally. Methods Patients admitted with a traumatic thoracic aortic injury between 2005 and 2011 were identified in the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…With the high rate of reintervention among a subset of patients who have undergone previous thoracic aortic repair and TEVAR frequently used as first-line treatment of most thoracic aortic pathologic entities, describing the perioperative outcomes and risks with TEVAR after previous thoracic aortic repair has become imperative for the contemporary management of aortic pathologic entities. 1,2 In the present patient cohort, the mortality after TEVAR without previous repair was comparable to the reported rates. In addition, this rate did not differ for those who had undergone TEVAR after previous aortic repair.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…With the high rate of reintervention among a subset of patients who have undergone previous thoracic aortic repair and TEVAR frequently used as first-line treatment of most thoracic aortic pathologic entities, describing the perioperative outcomes and risks with TEVAR after previous thoracic aortic repair has become imperative for the contemporary management of aortic pathologic entities. 1,2 In the present patient cohort, the mortality after TEVAR without previous repair was comparable to the reported rates. In addition, this rate did not differ for those who had undergone TEVAR after previous aortic repair.…”
Section: Discussionsupporting
confidence: 86%
“…Thoracic endovascular aortic repair (TEVAR) has been increasingly used, and, in many cases, as first-line treatment of severe aortic pathologic entities such as dissections, aneurysms, and traumatic aortic injuries. [1][2][3][4] Because aortic disease can be chronic and progressive, a subset of patients exist who will require TEVAR after previous thoracic aortic repair. As many as 20% of patients who have undergone previous thoracic aortic repair will require reintervention, which could entail TEVAR.…”
mentioning
confidence: 99%
“…28, 29 Similar to previous studies assessing the role of endovascular repair, we found that TEVAR was more commonly performed in urban teaching hospitals. 3032 This was expected, as novel technologies and techniques such as TEVAR are typically introduced first to high volume academic centers.…”
Section: Discussionmentioning
confidence: 99%
“…17, 18 For rTAA patients, however, it is unknown whether the introduction TEVAR has broadened their treatment eligibility. 17 The purpose of this study was to assess national trends in the treatment of rTAA, focusing on the relative utilization and outcome of TEVAR, open repair, and nonoperative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, thoracic endovascular aortic repair (TEVAR) has prevailed as the first-line therapy for most aortic diseases involving the descending thoracic aorta as recommended by both U.S. and European society guidelines. [1][2][3] Several meta-analyses, large registry studies, and large single-center studies have consistently demonstrated favorable outcomes after TEVAR compared with open surgical repair for the treatment of several descending thoracic diseases in the short term, [4][5][6][7][8] but many of these studies lack detailed information about the patients' pathologic and clinical characteristics as well as midterm or long-term results. Also, very few studies have examined the effect of presenting disease on TEVAR outcomes.…”
mentioning
confidence: 99%